Comportamento dinâmico e hidrodinâmico de reator anaeróbio híbrido - Godinho, Jayson Pereira (2017)
The anaerobic digestion process is very important in the treatment of sewage, as it is an efficient, simple process and low cost of implementation, operation and maintenance. Although Brazil has provided consolidated anaerobic processes, sanitation is still poor in the country, and the optimization of anaerobic reactors aims to improve the viability, effectiveness and expansion of treatment systems for sewage. The aim of this research project is to evaluate the reactor's performance through dynamic and hydrodynamic behavior of hybrid anaerobic reactor (UAHB) with a range of hydraulic retention time (HRT) of 4 to 12 hours and COD (gross samples) 250 - 1250 mgO2L -1. The reactor, with a volume of 22.1 L was operated with support means corrugated rings of Polyvinyl chloride (PVC) and kept at room temperature, the influent feed, simulating the synthetic wastewater. the physicochemical parameters were analyzed: temperature of the liquid and air, pH, total alkalinity (TA), bicarbonate alkalinity (BA), volatile acids (VA), chemical oxygen demand (COD), biochemical oxygen demand (BOD ), Turbidity, Total Solids (TS), total suspended solids (TSS), nitrogen Total Kjeldahl (NTK-N), ammonia nitrogen (amon-N), nitrite (NO2-N), nitrate (NO3-N) and Total phosphorus (P). It evaluated the hydrodynamic behavior and the determination of hydraulic anomalies, the stimulus-response pulse technique with injection of the tracer eosin Y. At the end of the experiments, statistical analysis was performed to find the optimal operating condition as well as the statistical models for validation experiments. In all operating conditions it was observed that the UAHB Reactor became apparent dynamic equilibrium (ADE) with alkalinity production to neutralize the volatile acids produced in acetogenesis process of anaerobic digestion. The increased of organic loading rate resulted in increased efficiencies in the removal of COD (gross and filtered samples), BOD and Turbidity, but reduced removals of Total Solids and Total Suspended Solids. The decrease in HRT reduced the removal efficiencies of COD parameters (grosss and filtered samples), BOD, Total Solids, Total Suspended Solids and Turbidity. Regarding the hydrodynamic in all operating conditions was observed long tail effect, the flow regime inside the reactor UAHB was rated as complete mixing tanks in series (N-CSTR). The presence of dead zones in the reactor was checked, the hydraulic efficiency was averaged 65% for the three conditions and it was not possible to observe the presence of short circuits for the three HRT tested. For the statistical analysis of the central rotary compound design (CRCD), the optimum operating condition for the reactor was to HRT 12 h and COD (gross samples) 553 mgCOD.L-1.